Metagenomic analysis of mycobiome in wild and captivity Sumatran orangutans (Pongo abelii) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study analyzes the mycobiome in wild and captive Sumatran orangutans. Materials and Methods: Nine orangutan feces samples from the wild and nine from captivity were divided into three repeats from 11- to 15-year-olds in good health. The Illumina platform for analysis of ITS bioinformatics was used according to the Qiime2 and CCMetagen approaches. Results: Wild Sumatran orangutans include 53% Ascomycota, 38% uncultured fungi, and 4% Basidiomycota. Orangutans in captivity are 57% Ascomycota, 26% uncultured fungi, and 2% Basidiomycota. Based on genuslevel, uncultured Neurospora (31%), Penicillium (10%), Aspergillus (3%), Fusarium (3%), Candida (2%), Cutaneotrichosporon (2%), and Limonomyces (2%) are found in wild orangutans. The most prevalent genus among captivity orangutans is Aspergillus (32%), followed by fungal sp. (11%), Lasiodiplodia (18%), Devriesia (2%), and Sordariomycetes (2%). According to the Chao1 diversity index and Shannon and Simpson, there was no significant difference between wild and captive Sumatran orangutans. Conclusion: Neurospora is unique to wild Sumatran orangutans, although Aspergillus predominates in captive orangutans. We hypothesize that the gut mycobiome of wild orangutans will resemble that of orangutans in captivity. The excellent range of food sources in the forest does not result in the prevalence of fungi in the typical gut microbiome. J. Adv. Vet. Anim. Res., 10(2): 228–236, June 2023http://doi.org/10.5455/javar.2023.j673